JSE 28:1 whole issue - Erickson, Kathleen E (Journal of Scientific Exploration, 2014)
TABLE OF CONTENTS <!--[if gte mso 9]> 14.00 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Editorial 5 Editorial STEPHEN E. BRAUDE Research Articles 7 Stock Market Prediction Using Associative Remote Viewing by Inexperienced Remote CHRISTOPHER CARSON SMITH, DARRELL LAHAM, Viewers GARRET MODDEL 17 An Experimental Study for Reproduction of Biological Anomalies Reported in the Hoeven 1999 Crop Circle ELTJO H. HASELHOFF, ROBERT J. BOERMAN, JAN-WILLEM BOBBINK 35 Pre-Columbian Transoceanic Infl uences: Far-Out Fantasy, Unproven Possibility, or Undeniable Reality? STEPHEN C. JETT Historical Perspective 75 G. Stanley Hall on “Mystic or Borderline Phenomena CARLOS S. ALVARADO Essay 95 Anomalistics, Pseudo-Science, Junk Science,Denialism: Corollaries of the Role of Science in Society HENRY H. BAUER Letter to the Editor 112 Exaggerated Emphasis PETER A. MCCUE Book Reviews 113 UFOs, ETs, and Alien Abductions: A Scientist Looks at the Evidence by Don Donderi THOMAS E. BULLARD 123 Time Loops and Space Twists: How God Created the Universe by Fred Alan Wolf ALAN H. BATTEN 127 Science, the Self, and Survival After Death,Selected Writings of Ian Stevenson edited by Emily Williams Kelly ERLENDUR HARALDSSON 130 Essay Review: Medical Mysteries and Conundrums—When Doctors May Not Help. Understanding Hashimoto’s Encephalopathy: A Guide for Patients, Families, and Caregivers by Nicola Nelson, Susan Foley, and Shari Lawler for the Hashimoto’s Encephalopathy SREAT Alliance HENRY H. BAUER 138 Thinking Fast and Slow by Daniel Kahneman TANA DINEEN 142 Dogmatism in Science and Medicine: How Dominant Theories Monopolize Research and Stifl e the Search for Truth by Henry H. Bauer DONALD J. DEGRACIA 149 Dogmatism in Science and Medicine: How Dominant Theories Monopolize Research and Stifl e the Search for Truth by Henry H. Bauer BRIAN JOSEPHSON 153 Science and the Afterlife Experience: Evidence for the Immortality of Consciousness by Chris Carter JAMES G. MATLOCK 160 Medical Qigong: Fact or Fiction? Chinese Medical Qigong edited by Tianjun Liu and Kevin W. Chen KENNETH S. COHEN Further Books of Note 172 The Man Who Filmed Nessie: Tim Dinsdale and the Enigma of Loch Ness by Angus Dinsdale HENRY H. BAUER 173 Breaking Convention: A Multidisciplinary Conference on Psychedelic Consciousness edited by Cameron Adams, Anna Waldstein, Ben Sessa, David Luke, and David King RICK STRASSMAN 174 Education in Parapsychology: Student and Instructor Perspectives by Harvey J. Irwin CAROLINE WATT 175 Science and the Citizen: ContemporaryIssues and Controversies edited by Marco Mamone Capria HENRY H. BAUER SSE News 176 SSE Masthead 177 Index of Previous Articles in JSE 193 Order forms for JSE Issues, JSE Subscriptions, and Society Membership 196 SSE 33rd Annual Conference Announcement, San Francisco 198 SSE 10th Euro Conference Announcement, Leiden, The Netherlands 214 Instructions for JSE Authors